Health promotion programs related to the Athens 2004 Olympic and Para Olympic games - Hadjichristodoulou Christos; Soteriades Elpidoforos S; Kremastinou Jeni; Chelvatzoglou Fotini C; Minogiannis Panagiotis S; Falagas Matthew E (BMC, 2006)
Abstract Background The Olympic Games constitute a first-class opportunity to promote athleticism and health messages. Little is known, however on the impact of Olympic Games on the development of health-promotion programs for the general population. Our objective was to identify and describe the population-based health-promotion programs implemented in relation to the Athens 2004 Olympic and Para Olympic Games. Methods A cross-sectional survey of all stakeholders of the Games, including the Athens 2004 Organizing Committee, all ministries of the Greek government, the National School of Public Health, all municipalities hosting Olympic events and all official private sponsors of the Games, was conducted after the conclusion of the Games. Results A total of 44 agencies were surveyed, 40 responded (91%), and ten (10) health-promotion programs were identified. Two programs were implemented by the Athens 2004 Organizing Committee, 2 from the Greek ministries, 2 from the National School of Public Health, 1 from municipalities, and 3 from official private sponsors of the Games. The total cost of the programs was estimated at 943,000 Euros; a relatively small fraction (0.08%) of the overall cost of the Games. Conclusion Greece has made a small, however, significant step forward, on health promotion, in the context of the Olympic Games. The International Olympic Committee and the future hosting countries, including China, are encouraged to elaborate on this idea and offer the world a promising future for public health.